Onkologie und Sport - Gail S; Künzell S (Dynamic Media Sales Verlag, 2014)
Multiple repetition maximum strength tests are proper alternatives to the 1-RM strength test, particularly in the context of recreational sports. In contrast to the 1-RM strength test, limited research has been conducted into the reliability of multiple repetition maximum strength tests. Consequently, there is a shortage of standardized and evaluated test protocols for multiple repetition maximum strength tests in the practice and science of sports. Therefore, the aim of this study was to evaluate the reliability of a 5-repetition maximum strength test in recreational athletes. After a short preparation session 25 healthy recreational athletes (16 men, 9 women; 31.512.5 years, 177.39.1 cm, 73.213.4 kg; 17 strength training experienced, 8 strength training inexperienced) performed a 5-repetition maximum strength test for the lower body (leg press and leg curl) twice within 7 days on the same weekday and at the same time of day. There were no significant differences between test and retest (p>0.05), so that learning and habituation effects could be excluded. A very high intraclass correlation coefficient (ICC>0.90; p<0.001) was found for the total sample as well as all sub-samples (men, women, strength training experienced, strength training inexperienced). Moreover, the coefficients of variation were very low and ranged between 2.2 and 4.7%. In conclusion, the 5-repetition maximum strength test is a reliable measurement method in recreational sports.Key Words: leg curl, leg press, maximum strength, strength diagnostics, strength training, training load